Ban the Box in Higher Education: Lessons From Louisiana on Changing Laws and Leading Movements - Phoenix, Annie (Journal of contemporary criminal justice, 2021)
In 2017, Louisiana became the first state to pass legislation to remove criminal history questions from college applications, commonly known as ban the box in higher education. This victory hinged on the work of two advocates, Syrita Steib, Founder and Executive Director of Operation Restoration, and Annie Phoenix, PhD student at Tulane University and Co-founder of Operation Restoration. The following article is a reflection on the process to pass ban the box in higher education in Louisiana and lessons learned to support others to engage in criminal legal system reform. We hope that this article serves as inspiration for other women impacted by incarceration, and nonimpacted supporters to use their voices to fight for liberation and to end the collateral consequences that prevent people with convictions from accessing education and other opportunities.